Peran Manajemen Humas dalam Meningkatkan Kualitas Promosi Penerimaan Peserta Didik Baru di TK Dharma Wanita Singgahan Tuban TP. 2021/2022 - Nurul Novitasari; Nur Lailatul Fitri; Ati Ni’matur Rohmah (Program Studi Pendidikan Islam Anak Usia Dini, UIN Sunan Ampel Surabaya, 2022)
The reason for the research at TK Dharma Wanita Saringembat, this institution has a public relations management and has a quality education marketing strategy every year to attract users of educational services. This study uses a descriptive qualitative approach. Methods of data collection using observation, interviews, and documentation. The results of this study include: (1) the role of public relations management includes: a) making institutional programs b) helping to publish institutional programs c) being a mediator between school institutions and the community. (2) Public relations strategies in increasing the promotion of new student admissions include: planning stages a) creating a PPDB team b) determining the place, time, and cost c) selecting promotional media. Implementation stages a) establish cooperation or MOU b) distribution of brochures and pamphlets c) installation of banners d) apply social media. Evaluation stages a) holding an evaluation meeting according to a predetermined schedule 2) evaluating social media and PPDB programs that are less effective. (3) the constraints of public relations in improving the quality of promotion of new student admissions a) lack of admin staff b) the lack of social media applications owned.